Clinicopathological and neuroradiological presentation in an immuno-deficiency patient with central nervous system recurrence of Burkitt lymphoma: an extremely rare case with complete remission achieved twice after GMALL-B-ALL/NHL2002 and R-MIV protocols - Glinka, Piotr; Sobstyl, Michał; Rymkiewicz, Grzegorz; Karamon, Karol; Skowronek-Płachta, Monika; Acewicz, Albert; Błachnio, Katarzyna; Konecki, Robert; Chmielewski, Marcin (Folia Neuropathologica, 2025)
Burkitt lymphoma (BL) is a specific, rare (1-2% of all cases of lymphoma) and aggressive type of B-cell non-Hodgkin lymphoma. If BL recurs during treatment, it usually becomes drug-resistant to subsequent treatment regimens and the prognosis is very poor. We present an extremely rare case of recurrent BL infiltrating the central nervous system (CNS) in a 27-year-old HIV-infected patient who had completed GMALL-B-ALL/NHL2002 protocol treatment 4 months earlier. Radiological and neuropathological examinations of cerebral recurrence of BL, followed by specialized oncological treatment, were discussed. Currently, with antiretroviral therapy and intensive immunochemotherapy for the immunodeficiency-associated BL variant, disease recurrence in the CNS is extremely rare. The magnetic resonance imaging (MRI) findings and laboratory tests are unspecific, as shown in the present case. The final diagnosis can be established properly by performing image-guided stereotactic biopsy or flow cytometry with cytology examination of cerebrospinal fluid. After confirmation of isolated cerebral recurrence of BL, the patient received intensive treatment according to the R-MIV protocol and achieved a second complete remission.